RISK ASSESSMENT OF ROAD CONSTRUCTION PROJECTS USING EXPECTED VALUE MODEL - Naumovski Mihail; Lazarevska Marijana (My University, 2020)
Risks can occur during any phase of road construction project, they cannot be completely avoided, but with proper risk management model they can be put to minimum. Risk assessment enables proper project management and helps the road construction managers in the decision-making process in order to avoid or decrease the negative effects and/or outcomes of any possible negative risks. The Expected Value Model refers to risk assessment by determining the severity of the consequences caused by the risk itself. This paper presents the benefits of risk assessment for achieving a quality realization of road construction projects. The main goal is to show the application of The Expected Value Model (EVM) and its implementation on a road construction project.
Keywords: risk assessment; expected value model; road construction project